eROSITA detection of a cloud obscuration event in the Seyfert AGN EC 04570–5206 - Markowitz, Alex; Krumpe, Mirko; Homan, David; Gromadzki, Mariusz; Schramm, Malte; Boller, Thomas; Krishnan, Saikruba; Saha, Tathagata; Wilms, Jörn; Gokus, Andrea; Hämmerich, Steven; Winkler, Hartmut; et al. (Astronomy & Astrophysics, 2024)
Context. Recent years have seen broad observational support for the presence of a clumpy component within the circumnuclear gas around supermassive black holes (SMBHs). In the X-ray band, individual clouds can manifest themselves when they transit the line of sight to the X-ray corona, temporarily obscuring the X-ray continuum and thereby indicating the characteristics and location of these clouds. Aims. X-ray flux monitoring with Spectrum Roentgen Gamma extended ROentgen Survey with an Imaging Telescope Array (SRG/eROSITA) has revealed that in the Seyfert 1 active galactic nucleus (AGN) EC 04570−5206, the soft X-ray flux dipped abruptly for about 10−18 months over 2020−2021, only to recover and then drop a second time by early 2022. Here, we investigate whether these flux dips and recoveries could be associated with cloud occultation events. Methods. We complemented the eROSITA scans with multiwavelength follow-up observations, including X-ray/UV observations with Swift, XMM-Newton, and NICER, along with ground-based optical photometric and spectroscopic observations to investigate the spectral and flux variability. Results. XMM-Newton spectra confirm that the soft X-ray flux dips were caused by partial-covering obscuration by two separate clouds. The 2020−2021 event was caused by a cloud with column density near 1 × 1022 cm−2 and a covering fraction of roughly 60%. The cloud in the 2022 event had a column density near 3 × 1023 cm−2 and a covering fraction near 80%. The optical/UV continuum flux varied minimally and the optical emission line spectra showed no variability in Balmer profiles or intensity. Conclusions. The transiting gas clouds are neutral or lowly-ionized, while the lower limits on their radial distances are commensurate with the dust sublimation zone (cloud 1) or the optical broad line region (cloud 2). One possible explanation is a dust-free, outflowing wind with embedded X-ray clumps. These events are the first cloud obscuration events detected in a Seyfert galaxy using eROSITA’s X-ray monitoring capabilities.
CRIS-Team Scopus Importer:2024-04-26
Keywords: galaxies: active; galaxies: Seyfert; X-rays: galaxies